Evaluación del espectro antimicrobiano del cannabidiol, frente Streptococcus agalactiae, Staphylococcus aureus, Pseudomona aeruginosa y Escherichia coli mediante un estudio in vitro - Navarro Osorio, Dagmar Paola (2024)
Antibiotic resistance represents a growing challenge worldwide, sparking considerable interest from governments and health organizations worldwide. In response to this issue and following the guidelines of the World Health Organization (WHO) on the research of compounds of plant origin, the antimicrobial activity of Cannabidiol (CBD) against Streptococcus agalactiae, Staphylococcus aureus, Pseudomonas aeruginosa, and Escherichia coli was investigated. The methodology involved the application of the disk diffusion method, using CBD concentrations of 3%, 6%, and 9%, which were compared with the antibiotics Amoxicillin, Enrofloxacin, Gentamicin, and Oxytetracycline as positive controls. To determine the minimum inhibitory concentration, CBD concentrations of 0.0125%, 0.025%, 0.05%, 0.10%, 0.50%, and 1% were tested, which were also used to determine the minimum bactericidal concentration based on turbidity. The CBD extract obtained at the Molecular Biology Laboratory of the Universidad Estatal de Bolívar showed that, at a concentration of 9%, it presents the largest inhibition halos for S. agalactiae and S. aureus, although these results were lower than those observed in the positive controls. However, no activity was observed against P. aeruginosa or E. coli. Likewise, it was determined that the minimum inhibitory concentration for Gram-positive bacteria is 0.05%, which is also effective for the minimum bactericidal concentration.